Carnosine treatment largely prevents alterations of renal carnosine metabolism in diabetic mice - Peters, Verena; Schmitt, Claus P.; Groß-Weissmann, Marie-Luise (Amino acids, 2012)
Recently, we identified an allelic variant of human carnosinase 1 (CN1) that results in increased enzyme activity and is associated with susceptibility for diabetic nephropathy in humans. Investigations in diabetic (db/db) mice showed that carnosine ameliorates glucose metabolism effectively. We now investigated the renal carnosinase metabolism in db/db mice. Kidney CN1 activity increased with age and was significantly higher in diabetic mice compared to controls. Increased CN1 activity did not affect renal carnosine levels, but anserine concentrations were tenfold lower in db/db mice compared to controls (0.24 ± 0.2 vs. 2.28 ± 0.3 nmol/mg protein in controls; p < 0.001). Homocarnosine concentrations in kidney tissue were low in both control and db/db mice (below 0.1 nmol/mg protein, p = n.s.). Carnosine treatment for 4 weeks substantially decreased renal CN1 activity in diabetic mice (0.32 ± 0.3 in non-treated db/db vs. 0.05 ± 0.05 μmol/mg/h in treated db/db mice; p < 0.01) close to normal activities. Renal anserine concentrations increased significantly (0.24 ± 0.2 in non-treated db/db vs. 5.7 ± 1.2 μmol/mg/h in treated db/db mice; p < 0.01), while carnosine concentrations remained unaltered (53 ± 6.4 in non-treated vs. 61 ± 15 nmol/mg protein in treated db/db mice; p = n.s.). Further, carnosine treatment halved proteinuria and reduced vascular permeability to one-fifth in db/db mice. In renal tissue of diabetic mice carnosinase activity is significantly increased and anserine concentrations are significantly reduced compared to controls. Carnosine treatment largely prevents the alterations of renal carnosine metabolism.